Assessment of different marker systems for diversity analysis in monokaryotic lines of button mushroom strains using RAPDs, ISSRs, IRAPs and REMAPs - Gupta, Mamta; Kamal, Shwet; Barh, Anupam; Bairwa, Rakesh K; Sharma, V P (Mushroom Research, 2020)
Improvement of button mushroom is a specific area involving isolation of single spores and inter-mating of non-fertile spores to develop new cultivars. The breeding of Agaricus bisporus is complicated proposition because of its unusual secondary homothallic sexual behavior where majority of the basidia produce two spores, each containing two nuclei of opposite mating-type and only a few basidia are tri- or tetrasporic yielding homokaryotic/monokaryotic spores. There is no way to identify the lateras A. bisporus mycelium unlike other basidiomycetes lacks clamp connections and is multinucleate. The only promising method to identify non-fertile isolates is the cumbersome fruiting trial. Because of their mobility and activity, transposons have proved to be valuable markers for genetic diversity and variability. Use of outward facing primers of retro-element insertion sites, the IRAP technique, (or between retro elements and simple sequence repeats, the ISSR method) has been useful to provide multi-locus anonymous markers. The SSAP, IRAP and REMAP methods are multiplex and are used to generate several anonymous marker bands. The TEs are known to have strains/species specific signatures, which can be used for identification of non-fertile isolates in A.bisporus.Â In the present study, a total of 1000 single spore isolates were developed from 11 different strains of button mushroom and were evaluated for their fertility. A total of 33 SSIs were identified as non-fruiting and were characterized using different molecular marker systems like RAPDs, ISSRs, IRAPs and REMAPs. The study aimed to identify specific markers linked with fertility of single spore isolates and also the markers will be used to construct a linkage map of the hybrids developed using these non fertile single spore isolates.